2022
DOI: 10.3390/plants11060751
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Plant Growth-Promoting and Antifungal Activities of Three Endophytic Yeast Strains

Abstract: In this research, the biosynthetic and biocontrol potential of endophytic yeast to improve the growth and development of tobacco has been elucidated. Three yeast strains were enriched and isolated from different plant tissues. Partial sequence analysis of ITS5-5.8-ITS4 region of the nuclear ribosomal DNA with universal primers identified YD5, YE1, and YSW1 as Saccharomyces cerevisiae (S. cerevisiae), Zygosaccharomyces bailii (Z. bailii), and Saccharomyces kudriavzevii (S. kudriavzevii), respectively. When cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 79 publications
(90 reference statements)
1
3
0
Order By: Relevance
“…Hu et al (2022) concluded that Mortierella could significantly increase soil soluble organic carbon, available nitrogen and related enzyme activities, and interoperate with microorganisms. It has been shown that Candida has the ability to dissolve inorganic phosphorus and produce IAA, and has biological control and soil remediation functions, which can promote plant germination and R. simsii growth as well as increase resistance to adversity stresses (Petkova et al, 2022). This is generally consistent with the results of the present study.…”
Section: Effect Of Heat Stress On Soil Fungal Community and Its Assoc...supporting
confidence: 93%
“…Hu et al (2022) concluded that Mortierella could significantly increase soil soluble organic carbon, available nitrogen and related enzyme activities, and interoperate with microorganisms. It has been shown that Candida has the ability to dissolve inorganic phosphorus and produce IAA, and has biological control and soil remediation functions, which can promote plant germination and R. simsii growth as well as increase resistance to adversity stresses (Petkova et al, 2022). This is generally consistent with the results of the present study.…”
Section: Effect Of Heat Stress On Soil Fungal Community and Its Assoc...supporting
confidence: 93%
“…In addition, the abundance of the shared dominant genera Zygosaccharomyces and Aureobasidium increased significantly in 8- and 15-year-old peach soils, respectively. Zygosaccharomyces has been reported to be involved in the solubilization of soil insoluble phosphate, which may be related to the high phosphorus demand of 8-year-old peach trees ( Gizaw et al, 2017 ; Petkova et al, 2022 ). Moreover, 8-year-old peach trees may accumulate pathogenic fungi with increasing age, and Zygosaccharomyces also has the ability to produce siderophore compounds (iron (III) ion compounds) that inhibit the growth of fungal phytopathogens ( Hider and Kong, 2010 ; Petkova et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zygosaccharomyces has been reported to be involved in the solubilization of soil insoluble phosphate, which may be related to the high phosphorus demand of 8-year-old peach trees ( Gizaw et al, 2017 ; Petkova et al, 2022 ). Moreover, 8-year-old peach trees may accumulate pathogenic fungi with increasing age, and Zygosaccharomyces also has the ability to produce siderophore compounds (iron (III) ion compounds) that inhibit the growth of fungal phytopathogens ( Hider and Kong, 2010 ; Petkova et al, 2022 ). Aureobasidium has been shown to be effective against postharvest fruit pathogens ( Di Francesco et al, 2020 ; Podgórska-Kryszczuk, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many plants associated with yeasts were reported to possess plant growth promoting capabilities. For example, endophytic yeasts from agriculturally grown fruits produced IAA [100] , while endophytic yeasts from strawberry ( Fragaria × ananassa ) leaves and wheat ( Triticum aestivum ) seeds were positively identified for phosphate solubilization, siderophore production, proteolytic activity, and ammonia production [111] . The diversity of ascomycetous and basidiomycetous yeast species from duckweed may lead to potential and valuable applications.…”
Section: Discussionmentioning
confidence: 99%